2014
DOI: 10.1155/2014/293476
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Complication of Triple Therapy of Rivaroxaban, Prasugrel, and Aspirin: A Case Report and General Discussion

Abstract: Hemorrhagic side effects are the bane of oral anticoagulation. Despite careful selection of medications and close monitoring, some adverse events are unavoidable. The available literature about the risks of triple oral anticoagulation therapy versus dual antiplatelet therapy does not address all of the medication combinations currently available. This report describes a patient with atrial fibrillation and recent stent placement who developed severe, recurrent epistaxis on aspirin, prosugrel, and rivaroxaban. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…However, a recent review of epistaxis patients found a lack of studies including patients treated with DOAC and could not identify a direct comparison of patients under DOAC or VKAs . Only a few case reports about the management of patients with epistaxis on DOAC therapy exist . Although severe bleeding complications in DOAC patients are rare, epistaxis was found to be one of the most frequent minor bleeding complication in patients on DOAC therapy …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent review of epistaxis patients found a lack of studies including patients treated with DOAC and could not identify a direct comparison of patients under DOAC or VKAs . Only a few case reports about the management of patients with epistaxis on DOAC therapy exist . Although severe bleeding complications in DOAC patients are rare, epistaxis was found to be one of the most frequent minor bleeding complication in patients on DOAC therapy …”
Section: Introductionmentioning
confidence: 99%
“…2 Only a few case reports about the management of patients with epistaxis on DOAC therapy exist. 6,7 Although severe bleeding complications in DOAC patients are rare, epistaxis was found to be one of the most frequent minor bleeding complication in patients on DOAC therapy. 8 To our knowledge, no study has yet described the characteristics of ED patients with epistaxis during DOAC therapy, nor did we find a direct comparison of DOACs and VKAs in patients presenting with epistaxis.…”
mentioning
confidence: 99%
“…Renal impairment ( n = 7) was the most relevant pathophysiological factor contributing to the development of ADRs. Concerning the mechanism of interaction, PK DDIs were involved in seventeen cases [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ], PD DDIs in eight cases [ 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ] and PK/PD DDIs in three cases [ 88 , 89 , 90 ]. Bleeding ( n = 18) and thromboembolic events ( n = 7) were the two main ADRs described in these case reports.…”
Section: Resultsmentioning
confidence: 99%
“…8 Multiple recurrent episodes of epistaxis in that case following initiation of rivaroxaban were managed simply with pressure and nasal packing. Of note, as an oral direct factor Xa inhibitor, laboratory monitoring for rivaroxaban to determine the degree of anticoagulation is generally not warranted in the clinical setting.…”
Section: Accepted Manuscriptmentioning
confidence: 95%